2015
DOI: 10.1371/journal.ppat.1004640
|View full text |Cite
|
Sign up to set email alerts
|

Non-redundant and Redundant Roles of Cytomegalovirus gH/gL Complexes in Host Organ Entry and Intra-tissue Spread

Abstract: Herpesviruses form different gH/gL virion envelope glycoprotein complexes that serve as entry complexes for mediating viral cell-type tropism in vitro; their roles in vivo, however, remained speculative and can be addressed experimentally only in animal models. For murine cytomegalovirus two alternative gH/gL complexes, gH/gL/gO and gH/gL/MCK-2, have been identified. A limitation of studies on viral tropism in vivo has been the difficulty in distinguishing between infection initiation by viral entry into first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 60 publications
(106 reference statements)
2
82
0
Order By: Relevance
“…Second, while data presented here indicate that gH/gL/gO is important for infection of all cell types by cellfree HCMV, analyses of gO mutants suggested that cell-to-cell spread on epithelial or endothelial cells and monolayers does not require gH/gL/gO (33,34). Together, these observations are consistent with a recent in vivo study involving murine CMV, suggest- ing that gH/gL/gO is important for initial infection of mice but less important for subsequent spread to distal organs and tissues (61).…”
Section: Discussionsupporting
confidence: 87%
“…Second, while data presented here indicate that gH/gL/gO is important for infection of all cell types by cellfree HCMV, analyses of gO mutants suggested that cell-to-cell spread on epithelial or endothelial cells and monolayers does not require gH/gL/gO (33,34). Together, these observations are consistent with a recent in vivo study involving murine CMV, suggest- ing that gH/gL/gO is important for initial infection of mice but less important for subsequent spread to distal organs and tissues (61).…”
Section: Discussionsupporting
confidence: 87%
“…However, while gH/gL/gO is important for infection of all cell types by cell-free virus, cell-to-cell spread does not require gH/ gL/gO (10). This was already documented for murine CMV (MCMV) (25), although HCMV and MCMV are distinct viruses and the relevant roles of gO may be very different. In addition, gB activation in the case of cell-free HCMV infection might be different from gB activation for viral spreading and cell-cell fusion.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly to HCMV gO, murine and guinea pig cytomegalovirus (CMV) gO binds to gH/gL, and its deletion leads to a severely reduced cell-free infectivity (30,31), indicating that the function of gO is conserved among the various CMVs. An essential role of the gH/gL/gO complex for pathogenesis of murine CMV (MCMV) was recently demonstrated in a mouse model: a gO-deficient MCMV mutant was unable to establish infection in mice (32), indicating that gO plays a pivotal role for host-to-host transmission of CMV. Immunization of mice with gH/gL/gO leads to full protection from otherwise lethal MCMV infection (33).…”
mentioning
confidence: 99%